Kinase-anchoring proteins in ciliary signal transduction. Issue 8 (30th April 2021) - Gopalan, Janani; Wordeman, Linda; Scott, John D.
Abstract : Historically, the diffusion of chemical signals through the cell was thought to occur within a cytoplasmic soup bounded by the plasma membrane. This theory was predicated on the notion that all regulatory enzymes are soluble and moved with a Brownian motion. Although enzyme compartmentalization was initially rebuffed by biochemists as a 'last refuge of a scoundrel', signal relay through macromolecular complexes is now accepted as a fundamental tenet of the burgeoning field of spatial biology. A-Kinase anchoring proteins (AKAPs) are prototypic enzyme-organizing elements that position clusters of regulatory proteins at defined subcellular locations. In parallel, the primary cilium has gained recognition as a subcellular mechanosensory organelle that amplifies second messenger signals pertaining to metazoan development. This article highlights advances in our understanding of AKAP signaling within the primary cilium and how defective ciliary function contributes to an increasing number of diseases known as ciliopathies.